2018
DOI: 10.37358/rc.18.2.6128
|View full text |Cite
|
Sign up to set email alerts
|

Color Changes and Stainability of Complete Dentures Manufactured Using PMMA-TiO2 Nanocomposite and 3D Printing Technology-one year evaluation

Abstract: Color stability through wear and time, one of the most important esthetic factor, influencing patient�s acceptance of an acrylic removable prosthesis, was investigated in vivo in a limited number of studies and solely on prefabricated denture teeth.The aims of the present paper were to assess the color changes occurred with the commercially available PMMA for 3D printing technique, improved by doping with titania nanoparticles, and to evaluate the color stability and stainability of the PMMA with 0.4%TiO2 dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…The 3D printed dentures based on PMMA-TiO 2 nanomaterial that have been investigated showed acceptable clinical performance [30] after 18 months of permanent wearing of the medical devices. We consider that continuous reevaluations are requested for a more detailed long-term analysis of the complete dentures 3D printed from our proposed nanocomposites.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D printed dentures based on PMMA-TiO 2 nanomaterial that have been investigated showed acceptable clinical performance [30] after 18 months of permanent wearing of the medical devices. We consider that continuous reevaluations are requested for a more detailed long-term analysis of the complete dentures 3D printed from our proposed nanocomposites.…”
Section: Discussionmentioning
confidence: 99%
“…Also, our previous studies on including nanotitania in PMMA for 3D printed dentures revealed the antibacterial characteristics of the obtained polymer [9], as well as other improved properties including color stability, assessed under clinical conditions [32][33][34][35].…”
Section: Discussionmentioning
confidence: 84%
“…However, studies on the use of CAD/CAM additive technology with photo-cross-linkable polymers for long term removable complete denture manufacturing are scarce. A one-year evaluation of color changes and stainability of ten monolithic 3D printed complete dentures with 0.4 % nanotitania inclusions was performed by our team and the color changes measured over one year were below the maximum acceptability threshold, significantly lower as compared to the same PMMA without TiO 2 [14]. No evaluation was performed on the veneered denture base.…”
Section: Resultsmentioning
confidence: 99%